2022
DOI: 10.1039/d2ra06473a
|View full text |Cite
|
Sign up to set email alerts
|

Balanced change in crystal unit cell volume and strain leads to stable halide perovskite with high guanidinium content

Abstract: This study highlights that PbS QDs stabilize the target 15% guanidinium based perovskite solar cells due to a synergic combination of compressive strain and volume expansion of the MAPbI3 perovskite unit crystal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this work, we analyzed the incorporation of guanidinium (GA + ) cation during the synthesis of colloidal mixed-cation Cs 1– x GA x PbI 3 PNCs with improved optical performance and a lowered defective structure, suitable for the fabrication of efficient bright perovskite R-LEDs. Considering that some works report that high ratios of GA + result in the formation of 2D layered perovskites due to its big size, 30 32 here, we were able to establish that the addition of a percentage of GA + equal or lower than 30 mol % has been considered. This GA content was used to tailor the tolerance factor of CsPbI 3 PNCs looking for a stable black α-cubic phase perovskite, without altering the initial crystalline phase of the host.…”
Section: Introductionmentioning
confidence: 91%
“…In this work, we analyzed the incorporation of guanidinium (GA + ) cation during the synthesis of colloidal mixed-cation Cs 1– x GA x PbI 3 PNCs with improved optical performance and a lowered defective structure, suitable for the fabrication of efficient bright perovskite R-LEDs. Considering that some works report that high ratios of GA + result in the formation of 2D layered perovskites due to its big size, 30 32 here, we were able to establish that the addition of a percentage of GA + equal or lower than 30 mol % has been considered. This GA content was used to tailor the tolerance factor of CsPbI 3 PNCs looking for a stable black α-cubic phase perovskite, without altering the initial crystalline phase of the host.…”
Section: Introductionmentioning
confidence: 91%
“…The benets of guanidium cations are attributed to their strong hydrogen bonding ability with the surface halides, which in turn facilitates the surface defect recovery. [58][59][60][61] 3D/2D core/shell perovskites are regarded as multidimensional perovskites, where Chen et al revealed that the multidimensional type-I heterostructure formation between 3D MAPbBr 3 and 2D (octylammonium) 2 PbBr 4 leads to multiphoton absorption, which are useful for multiphoton imaging applications. 62 In a recent report by Ye et al, 25 spin-polarised luminescence behaviour has been studied, where a chiral organic ammonium bromide molecule is introduced to provide a 2D perovskite layer coating, which formed a 3D/2D core/shell with a type-II heterostructure.…”
Section: Semiconductor/semiconductor Heterostructurementioning
confidence: 99%
“…[24][25][26] The additions of guanidinium (GA), which has a larger ionic radius than EA, has improved the crystallinity and grain sizes of perovskite compounds. [27][28][29][30][31] Furthermore, it is reported that the low-dimensional perovskite film formed by introducing a mixed cation of GA and octylammonium as a passivation layer at the perovskite/hole transport layer interface provided a smooth surface, contributing to reduce carrier recombination and to enhance charge extraction. 32) There have been a number of studies on formamidinium (FA) based perovskites, 33) and the band structure of MAPbI 3 and FAPbI 3 has been investigated by first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%